The moderating role of parent–child interaction in the relationship between maltreatment and psychological well-being among preschool children - Zhang, Cheng; Huang, Chuican; Zhang, Chunhui; Wu, Weijia; Huang, Zhenning; Xia, Xue; Liu, Sijia; Wang, Chen; Luo, Qing; Fan, Lichun (Frontiers in Psychology, 2025)
ObjectiveThis study aimed to examine the relationship between maltreatment and psychological well-being among preschool children and explore parent–child interaction’s moderating role on this association.MethodsThis study employed a cross-sectional design and multistage stratified cluster random sampling method. Between December 2022 and January 2023, 180 kindergartens in the Hainan province—encompassing 4,886 newly enrolled children as participants—were selected. All data were collected using an online platform, on which parents or caregivers reported their children’s history of abuse and completed the Strengths and Difficulties Questionnaire and Chinese Parent–Child Interaction Scale.ResultThe reporting rate of child abuse in Hainan Province was 61.81%. Specifically, frequent physical abuse (odds ratio [OR] = 1.44, 95% confidence interval [CI] = 1.15–1.80), occasional physical neglect (OR = 1.75, 95% CI = 1.37–2.11), frequent physical neglect (OR = 1.57, 95% CI = 1.31–1.87), and frequent emotional abuse (OR = 1.57, 95% CI = 1.31–1.87) were associated with a higher overall rate of difficulties. Frequent physical abuse (OR = 1.33, 95% CI = 1.08–1.64) and frequent emotional abuse (OR = 1.36, 95% CI = 1.16–1.61) were correlated with a higher rate of prosocial problems. A significant interaction was observed between parent–child interaction and occasional physical neglect on psychological well-being (OR = 0.73, 95% CI = 0.54–0.98, p = 0.035).ConclusionPreschool children who experience maltreatment exhibit an increased risk of developing psychological health issues, indicating a cumulative effect. Our study indicates that positive parent–child interaction mitigates occasional physical neglect’s negative impact on preschool children’s psychological well-being but does not exhibit a moderating effect on frequent physical neglect or other forms of maltreatment.